Adapting isokinetic dynamometry to accommodate transradial amputation: The development of a new dynamometer attachment and user case study. Issue 1 (1st January 2019) - Chouinard, Jessica; Chester, Victoria; Kuruganti, Usha
Abstract: Upper limb amputations can significantly impact daily functions and affect quality of life. Significant advances over the last few decades have resulted in lighter and stronger artificial limbs; however, users have indicated that improved function and control strategies are desirable to become more in line with able-bodied limb function. The complexity of the amputated limb muscle physiology makes quantitative clinical assessment challenging. In addition, most clinical research has focused on studying isometric (stationary) limb movements. In order to develop more robust systems, it is critical to study muscle mechanics of those with amputations under dynamic (moving) movements. One method of safely examining dynamic movements is the use of isokinetic dynamometers. These machines allow measurement of upper and lower extremity isokinetic movements at controlled angular velocities while ensuring no stress is placed on the individual (even if the participant is unable to move the lever arm). For able-bodied participants, this doesn't present a problem. However, there is currently no commercially available isokinetic dynamometer adapter for prosthesis users. The purpose of this project was to develop an adapter for those with amputations to safely and effectively operate the dynamometer. The adapter was tested by one clinical patient to determine its effectiveness.